Comparison of fine‐needle aspiration and fine‐needle capillary sampling of thyroid nodules: A prospective study with emphasis on the influence of nodule size. Issue 4 (3rd December 2013) - Zhou, Jian‐Qiao; Zhang, Jing‐Wen; Zhan, Wei‐Wei; Zhou, Wei; Ye, Ting‐Jun; Zhu, Ying; Yao, Jie‐Jie; Liu, Jun; Hu, Yun‐Yun; Grant, Edward G.
Abstract : BACKGROUND: The objective of this study was to compare the sampling efficiency of ultrasound‐guided fine‐needle aspiration (FNA) and fine‐needle capillary (FNC) sampling in thyroid nodules, in which the authors specifically analyzed the influence of nodule size. METHODS: This study included 280 thyroid nodules in 275 consecutive patients. The nodules were divided into 4 size subgroups: ≤5.0 mm, from 5.1 to 10.0 mm, from 10.1 to 20.0 mm, and >20.0 mm. Each nodule was sampled by both FNA and FNC. The final cytopathologic findings were reported. The smears were scored and then categorized as diagnostically inadequate, adequate, or superior on the basis of 4 parameters, which included background clot or blood, the number of obtained cells, preserved tissue architecture, and cellular degeneration. RESULTS: The κ scores for agreement of the cytopathologic results between FNA and FNC sampling in the 4 size subgroups were 0.377, 0.455, 0.751, and 0.352 for nodules that measured ≤5.0 mm, from 5.1 to 10.0 mm, from 10.1 to 20.0 mm, and >20.0 mm, respectively. The proportion of nondiagnostic of FNAs was significantly lower than the proportion of nondiagnostic FNC samples in nodules that measured >20.0 mm ( P  = .037). Scores for the 4 diagnostic parameters were significantly greater in FNAs than in FNC samples in nodules that measured from 5.1 to 10.0 mm and >20.0 mm (all P  < .05); however, similar results were not observed in the nodules that measured ≤5.0 mm or from 10.1 to 20.0 mm (all P  > .05). Also, FNA yielded significantly more diagnostically superior specimens than FNC sampling in nodules that measured from 5.1 to 10.0 mm and >20.0 mm ( P  < .05 for both). CONCLUSIONS: The current findings indicated that FNA may be more suitable than FNC for sampling nodules that measure from 5.1 to 10.0 mm and >20.0 mm; whereas, for nodules that measure ≤5.0 mm and from 10.1 to 20.0 mm, the 2 techniques could yield specimens with similar quality. Cancer (Cancer Cytopathol) 2014;122:266–273 . © 2013 American Cancer Society . Abstract : Fine‐needle aspiration may be more suitable than fine‐needle capillary sampling for thyroid nodules that measure from 5.1 to 10.0 mm and 20.0 mm. For nodules that measure from 10.1 to 20.0 mm and 5.0 mm, the 2 techniques may yield specimens with similar quality.